Mechanoredox Catalysis Enables a Sustainable and Versatile Reversible Addition‐Fragmentation Chain Transfer Polymerization Process. (7th December 2022) - Chakma, Progyateg; Zeitler, Sarah M.; Baum, Fábio; Yu, Jiatong; Shindy, Waseem; Pozzo, Lilo D.; Golder, Matthew R.
Abstract: The sustainable synthesis of macromolecules with control over sequence and molar mass remains a challenge in polymer chemistry. By coupling mechanochemistry and electron‐transfer processes (i.e., mechanoredox catalysis), an energy‐conscious controlled radical polymerization methodology is realized. This work explores an efficient mechanoredox reversible addition‐fragmentation chain transfer (RAFT) polymerization process using mechanical stimuli by implementing piezoelectric barium titanate and a diaryliodonium initiator with minimal solvent usage. This mechanoredox RAFT process demonstrates exquisite control over poly(meth)acrylate dispersity and chain length while also showcasing an alternative to the solution‐state synthesis of semifluorinated polymers that typically utilize exotic solvents and/or reagents. This chemistry will find utility in the sustainable development of materials across the energy, biomedical, and engineering communities. Abstract : Coupling mechanochemistry and single‐electron transfer processes in a ball mill facilitates an efficient reversible addition‐fragmentation chain transfer polymerization reaction. A versatile mechanoredox process is developed to synthesize macromolecules with good molar mass control. This method serves as an alternative to access complex polymers that may be difficult to access using traditional solution‐state processes.